On Еc-Continuous and δ-ßc-Continuous Mappings in Topological Spaces Via Еc-open and δ-ßc-open sets - Abdulwahid, Sarah. H.; AL. Jumaili, Alaa. M. F. (Iraqi Journal of Science, 2022)
In the present paper, new concepts of generalized continuous mappings, namely Еc and δ-ßc-continuous mappings have been introduced and studied by using a new generalized of open sets Еc and δ-ßc-open sets ,respectively. Several characterizations and fundamental properties of these forms of generalized continuous mappings are obtained. Moreover, the graphs of Еc-continuous and δ-ßc-continuous mappings have been investigated. In addition, the relationships among Еc-continuous and δ-ßc-continuous mappings and other well-known forms of generalized continuous mappings in topological spaces are also discussed.